Circulating CD3+HLA-DR+ Extracellular Vesicles as a Marker for Th1/Tc1-Type Immune Responses - Ryutaro Oba; Motomichi Isomura; Akira Igarashi; Kinya Nagata (Journal of Immunology Research)
Extracellular vesicles (EVs) are known to contain unique proteins that reflect the cells of origins. Activated T cells are reported to secrete various EVs. To establish T cell subset-specific biomarkers, we performed proteomic analysis with Th1- and Th2-derived EVs and identified HLA-DR as a Th1-dominated EV membrane protein. We designed a measurement system for CD3+CD4+, CD3+CD8+, and CD3+HLA-DR+ EVs to specifically determine EV subpopulations derived from CD4+, CD8+, and Th1-type T cells, respectively. In vitro analysis showed that CD3+CD4+ EVs and CD3+CD8+ EVs were selectively secreted from activated CD4+ and CD8+ T cells, respectively, and that CD3+HLA-DR+ EVs were actively secreted from not only Th1 but also activated CD8+ T (probably mostly Tc1) cells. To evaluate the clinical usefulness of these EVs, we measured the serum levels in patients with inflammatory diseases, including Epstein-Barr virus (EBV, n=13) infection, atopic dermatitis (AD, n=10), rheumatoid arthritis (RA, n=20), and osteoarthritis (OA, n=20) and compared the levels with those of healthy adults (n=20). CD3+CD4+ EVs were significantly higher in all of EBV infection, AD, RA, and OA while CD3+CD8+ EVs were higher in EBV infection, lower in RA, and not different in AD and OA relative to the control. The levels of CD3+HLA-DR+ EVs were markedly higher in EBV infection and significantly lower in AD. The results suggest that these EV subpopulations reflect in vivo activation status of total CD4+, total CD8+, and Th1/Tc1-type T cells, respectively, and may be helpful in T cell-related clinical settings, such as cancer immunotherapy and treatment of chronic infection, autoimmune diseases, and graft-versus-host disease.